2014
DOI: 10.7554/elife.01879
|View full text |Cite|
|
Sign up to set email alerts
|

Membranes linked by trans-SNARE complexes require lipids prone to non-bilayer structure for progression to fusion

Abstract: Like other intracellular fusion events, the homotypic fusion of yeast vacuoles requires a Rab GTPase, a large Rab effector complex, SNARE proteins which can form a 4-helical bundle, and the SNARE disassembly chaperones Sec17p and Sec18p. In addition to these proteins, specific vacuole lipids are required for efficient fusion in vivo and with the purified organelle. Reconstitution of vacuole fusion with all purified components reveals that high SNARE levels can mask the requirement for a complex mixture of vacu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
97
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(97 citation statements)
references
References 57 publications
0
97
0
Order By: Relevance
“…Even with trans-SNARE pairing linking apposed membranes, the rate of fusion is strongly enhanced by the presence of a tether, whether the physiological Ypt7-HOPS tether or a synthetic tether such as polyethylene glycol (17). In either case, small-headgroup lipids, which lower the energy for membrane transitions through nonbilayer intermediates, are required for meaningful fusion rates (25). We now report that Sec17 can dramatically accelerate fusion once trans-SNARE pairs have assembled.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…Even with trans-SNARE pairing linking apposed membranes, the rate of fusion is strongly enhanced by the presence of a tether, whether the physiological Ypt7-HOPS tether or a synthetic tether such as polyethylene glycol (17). In either case, small-headgroup lipids, which lower the energy for membrane transitions through nonbilayer intermediates, are required for meaningful fusion rates (25). We now report that Sec17 can dramatically accelerate fusion once trans-SNARE pairs have assembled.…”
Section: Discussionmentioning
confidence: 87%
“…To optimize the stimulation by Sec17, we varied the lipid composition of the proteoliposomes. We have recently reported that acidic lipids (24) and small-headgroup lipids (25) Proteoliposomes of only PC and PS were less active than those of vacuolar lipid composition but were strongly stimulated by the addition of Sec17 (Fig. 2B) in the absence of Sec18 or ATP.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1E). Although we cannot rule out other mechanisms of lipid transfer between cells, such as asymmetric lipid transfer or transient membrane rupture followed by reannealing (32), the extensive lipid mixing most likely reflects a deficit of the GPI-linked SNARE complexes in destabilizing the lipid bilayers and opening a fusion pore. If lipid-anchored STX11 mainly promotes incomplete fusion, how can it be essential for degranulation and cell-mediated cytotoxicity in CTLs and NK cells?…”
Section: Resultsmentioning
confidence: 99%